2020
DOI: 10.48550/arxiv.2012.00965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurements of undulator radiation power noise and comparison with $\textit{ab initio}$ calculations

Ihar Lobach,
Sergei Nagaitsev,
Valeri Lebedev
et al.

Abstract: Generally, turn-to-turn fluctuations of synchrotron radiation power in a storage ring depend on the 6D phase-space distribution of the electron bunch. This effect is related to the interference of fields radiated by different electrons. Changes in the relative electron positions and velocities inside the bunch result in fluctuations in the total emitted energy per pass in a synchrotron radiation source. This effect has been previously described assuming constant and equal electron velocities before entering th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Primary sources of this noise were the integrator's op-amp and the oscilloscope's pre-amp. In [21], we showed that this noise level was independent of N via measurements with an independent test light source. Therefore, it can be simply subtracted.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Primary sources of this noise were the integrator's op-amp and the oscilloscope's pre-amp. In [21], we showed that this noise level was independent of N via measurements with an independent test light source. Therefore, it can be simply subtracted.…”
mentioning
confidence: 87%
“…where k is the magnitude of the wave vector, θ x and θ y represent the horizontal and vertical angles of the direction of the radiation in the paraxial approximation, C is a constant. Then [10,21]…”
mentioning
confidence: 99%
See 3 more Smart Citations